Flood Modelling of Madi River Using HEC-RAS by Rain on Grid Approach - Thapa, Prasun; Manandhar, Sujal; Poudel, Swikriti; Shrestha, Sudesha; Pakhrin Tamang, Shila; Shrestha, Roshani; Devkota, Nirajan (KEC Journal of Science and Engineering, 2024)
Indispensable for prognosticating flood impact in areas with limited data availability, reliable flood models are crucial for the analysis and mitigation of flood hazard. This study provides insight to accurately analyse flood scenarios by preparing a well calibrated 2D hydraulic model in HEC-RAS along with the Rain on Grid approach, which is subsequently used for hazard map preparation of Madi River. Hazard classification of flood depth indicated that for a 20-year return period, Moderate hazard levels covered 16.499%, High hazard levels covered 14.831%, and Very High hazard levels covered 68.670% of the total inundated area with reference to the depth hazard categories. Since, significant portion of the inundated area is classified as Very High Hazard; the finding of this research emphasizes the need of effective mitigation measure and provides essential insights crucial for flood risk assessment.